Continuous integration C# and Github actions and codespaces. (Pragmatic AI Solutions, 2022)
Learn to use Github CodeSpaces and Github Actions to Build and Test C# and XUnit projects. 00:00 Intro 01:03 Create Github Project for C# 01:27 Create Github Codespace 16 core Visual Studio environment 03:15 Create Xunit project with dotnet cli 04:04 Create XUnit test 04:40 Find build and test commands for project 06:51 Setup and run GitHub Actions project 08:04 Verify Github Actions Compiles and Tests C#.